Intestinal microflora on physical performance in athletes - a comprehensive review - Kucharczyk, Natalia; Półtorak, Katarzyna; Filarski, Wiktor; Markowicz, Zofia; Gaweł-Dąbrowska, Dagmara (Journal of Education, Health and Sport, 2025)
Introduction: The intestinal microflora is a crucial component of the human body, developing in parallel with the host and playing a pivotal role in maintaining health throughout life. The composition of the microbiota is dynamic, influenced by factors such as genotype, diet, and initial colonization at birth, resulting in a unique microbiotic profile for each individual. The gut microbiota supports a variety of physiological functions, including immune modulation, nutrient metabolism, and the synthesis of essential vitamins and neurotransmitters. Importantly, it maintains homeostasis, through the bidirectional communication system between intestines and central nervous system, which is necessary for all forms of physical performance. Purpose of the work: The purpose of this study is to review the effects of intestinal microflora on physical performance and endurance in athletes. Special attention is given to the influence of dietary supplements, which can have an impact on composition of the microflora. Materials and methods: A comprehensive analysis of research articles available on PubMed, Google Scholar, Web of Science, Embase, and Scopus was conducted using search terms related to: "intestinal microflora," "physical performance," "gut-brain axis," "athletes" and "physical training." Results: The intestinal microflora is linked to the increased performance during physical exercise in athletes. Understanding this influence on the health and physical ability of athletes will allow better results in competitions and endurance.